Labyrinthus iudiciorum in illegal occupation of houses: remedies under criminal and civil law and analysis of their effectiveness - Lafuente Torralba, Alberto José (Revista de derecho aragonés, 2021)
In this article we make a practical study about illegal occupation, which has been exacerbated by economic crisis and the increase of emergency housing situations. More precisely, the author intends to analyse existing procedural instruments under criminal and civil law. Moreover, we take stock and critically evaluate the effectiveness of these instruments, identifying their dysfunctions and making improvement proposals. We pay particular attention to the latest developments which has been incorporated by the legislation in this field: Law 5/2018, on amending Civil Procedural Law in relation to illegal ocuppation of houses; Royal Decree-law 37/2020, for urgent measures to face social and economical vulnerabilities in the area of housing; Instruction 1/2020 of Prosecutor General’s Office, about action criteria to request precautionary measures in burglary and takeover of inoccupied properties; and Instruction 6/2020 of State Secretariat for Security, which establishes the action protocol for State Security Forces in the face of illegal occupation of properties.